2017
DOI: 10.5194/ars-15-99-2017
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal frequency division multiplexing with amplitude shift keying subcarrier modulation as a reliable and efficient transmission scheme for self-mixing receivers

Abstract: Abstract. A new receiving scheme for self-mixing receivers is presented that overcomes the disadvantages of the selfheterodyne concept. Generally speaking, the self-mixing receiver offers immunity to phase noise and frequency offsets, especially at very high frequencies, since it does not require radio frequency local oscillators. Our proposed technique eliminates the drawbacks of the self-heterodyne transmission scheme, which are the poor power efficiency and the strong dependence on the continously transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Special signal schemes have to be employed to enable the reconstruction of the receive signal after selfmixing, e.g. the self-heterodyne transmission technique [10]- [13]. Recently, it was found that self-mixing arrays offer a large receive gain over a wide angular range which is not possible for reciprocal antenna systems with super-heterodyne receivers [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Special signal schemes have to be employed to enable the reconstruction of the receive signal after selfmixing, e.g. the self-heterodyne transmission technique [10]- [13]. Recently, it was found that self-mixing arrays offer a large receive gain over a wide angular range which is not possible for reciprocal antenna systems with super-heterodyne receivers [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…in optics [30]- [36] or acoustic underwater communications [37]- [39]. Recent research in the field of self-heterodyne transmission techniques concentrates on studying the effects of self-mixing arrays [19] and on improving the transmission technique on a signal processing level [40]- [44] or even on extending the self-mixing technique to a more general approach without an explicitly transmitted carrier signal [45]. Also, the analogue receiver circuit can be improved as compared to a simple square-law detector by employing the self-coherent technique [46].…”
mentioning
confidence: 99%